TECHNICAL EFFICIENCY ANALYSIS OF MILKFISH POND FARMING (CHANOS CHANOS F) IN JANGKA DISTRICT OF BIREUEN REGENCY - Adhiana; Riani; Maulina (CV. Radja Publika, 2023)
This study examines efforts to increase milkfish production through technical efficiencycarried out in the District of Jangka, Bireuen Regency. The population was all milkfish pond farmers in the Jangka District, and the number of samples in this study were 78 milkfish pond farmers using a random sampling method. This research uses primary data and secondary data. Data were analyzed using the stochastic frontier method and analyzed descriptively qualitatively. The research objective is(1) analyze the factors of land area, labor, logs, fertilizers, feed and pesticides for milkfish pond farming, and (2)analyzethe level of technical efficiency of milkfish pond farming in the Jangka District of Bireuen Regency.The research results are therethe five production factors of milkfish pond farming, namely land area, labor, spindles, fish feed and pesticides which have a significant effect on milkfish production while the fertilizer variable has no significant effect on milkfish production. On average, milkfish pond farmers in the Jangka District of Bireuen Regency are technically efficient. However, farmers still have the opportunity to further increase efficiency, through the use of production factors according to their needs.It is recommended for further research to use more diverse variables so as to provide better results.